Monitoring the agri-food system in Myanmar: Food vendors - March 2022 - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
This Research Note presents the results of recent interviews with food vendors in rural and urban areas and in all state/regions of Myanmar as a part of the Myanmar Household Welfare Survey (MHWS) telephone survey (MAPSA 2022a). The purpose of the food vendor component of the MHWS is to provide data and insights to interested stakeholders in order that they better understand the effects of shocks related to COVID-19 and the ongoing political crisis on Myanmar’s food markets. In particular, the note explores (nominal) prices of foods and difficulties in food vendor operations due to the COVID-19 and political crises.